P188 Doc*x the danish occupational cohort – a new open research database on occupational medicine. (1st September 2016) - Flachs, Esben Meulengracht; Petersen, Sesilje Elise Bondo; Schlünssen, Vivi; Hansen, Johnni; Kolstad, Henrik Albert; Svendsen, Susanne Wulff; Budtz-Jørgensen, Esben; Fallentin, Nils; Andersen, Johan Hvid; Bonde, Jens Peter Ellekilde
Abstract : DOC*X is a Danish nationwide individual level database on exposures in the occupational environment containing information on labour market affiliation, industry, and job type, covering all work active residents in Denmark from 1970 to 2012, around 6.2 million people. DOC*X is an open research database, aiming to provide access to high quality data for both Danish and international researchers in occupational health. The database is built upon a large number of administrative registers, and provides possibilities for linking occupational environment and health during a period of more than 40 years. The number of employed persons varies between 2.0 and 2.7 million per year whereof job and industry could be identified for around 75%. Job and industry categorisation is harmonised across years according to slightly amended versions of ISCO-88 and NACE-rev. 2. DOC*X occupational exposure assessment will be based upon currently developed and revised job-exposure matrices (JEMs), describing various exposures according to job types and industries. DOC*X will in a short time contain JEMs on noise, sunlight and UV-radiation, dust (organic and inorganic components), biomechanical workload, prolonged sedentary work, psychosocial factors, and selected chemical agents. DOC*X has in addition to information on occupation, information on migration, retirement, mortality, hospitalisations, cancer morbidity, and a wide range of other health and social security services. The amount of health related outcomes available varies: Mortality and cancer are virtually complete for all years, whereas other health and social security services are introduced during the period. However all outcomes are drawn from nationwide registers, and have exceedingly good coverage when available. In conclusion, the DOC*X database gives unique possibilities to investigate, how the occupational environment affects health. More information on the DOC*X database and on access to data may be found at www.doc-x.dk/en/ .